The Effect of Structured Peer-to-Peer Interactions on Conceptual Understanding of DC Resistive Circuits in Secondary Physics - Crowe, Jacalyn (Tufts Archival Research Center, 2005)
A qualifying paper submitted in partial fulfillment of the requirements for the degree of Doctor of Philosophy in Science Education. Abstract: This study examined the prevalence and persistence of some common misconceptions about DC resistive circuits and the role of social interaction in promoting changes in students' views. It explored the types of interactions that were common in student dialogues as they discussed conceptual questions and whether the number of correct responses to these conceptual questions significantly increased as a result of discussions with peers. Analysis of interactions revealed that the most common student statements during the discussion phase could be characterized as either simply stating their answer or as providing the reasoning behind their answer choice.